THE FRAMEWORK MODEL OF DIGITAL COOPERATIVE TO EXPLORE ECONOMIC POTENTIAL IN HIGHER EDUCATION - Hasbullah Hasbullah; Salleh Ahmad Bareduan (SINERGI, 2021)
In February 2020, the Indonesian Ministry of Cooperatives and SMEs noted that in the last four years, 81,686 cooperatives were dissolved, leaving 123,048 active cooperatives. This case is a huge challenge for the government to overcome.  Indonesian Internet Service Providers Association (APJII) stated that the number of internet users in Indonesia reached 196.7 million in the middle of 2020. Meanwhile, data from Google & Temasek showed purchasing products via e-Commerce in Indonesia reached US$ 10.9 billion in 2017 and continuously increased in 2020. Most cooperatives in Indonesia run business conventionally with manual transactions, limited time, traditional logistics, and conventional membership administration. Nowadays, the institution with tens of thousands of members no longer effectively runs cooperative conventionally in a disruptive era. A conventional cooperative at a private university in Jakarta was observed in the study. There are tens of thousands of students and staff at the university. Three research questions arise, such as what can not be adequately solved in a traditional cooperative, what tools are used in digital cooperatives, and what shape can be used in the digital cooperative system model to solve issues. This study proposes a framework model in developing a digital cooperative to accommodate a huge amount of membership and enhance business scope. The research identified technology needed to overcome matters cannot be dealt with in a conventional cooperative. It provided a  digital cooperative frameworks model that impacts value creation, value capture, and value delivery, especially in higher education.